Changes in the body image of bone sarcoma survivors following surgical treatment—A qualitative study. Issue 2 (29th December 2015) - Fauske, Lena; Lorem, Geir; Grov, Ellen K.; Bondevik, Hilde
Abstract : Background and Objectives: Among several long‐term effects, people treated for cancer may experience an altered appearance. Our study aims to identify how visible body changes following surgical treatment affect the life and identity of primary bone sarcoma survivors 3–10 years after diagnosis. A qualitative, phenomenological, and hermeneutic design was applied. Methods: Sarcoma survivors (n = 18) who were previously treated at Norwegian Radium Hospital, Oslo University Hospital, participated in the study. In‐depth and semi‐structured interviews were conducted and analyzed using inductive thematic analysis. Results: The main finding of this study concerned how altered appearance after bone cancer treatment in the hip/pelvis or lower extremities affected the participants' self‐esteem. Half of the participants expressed concerns about their visible differences, particularly those with functional impairment. They felt that it is important to hide the bodily signs of changes to appear as normal as possible, as well as attractive and healthy. They describe, with specific examples, how these changes influence their self‐realization, especially their social life. Conclusions: Healthcare providers who guide bone sarcoma survivors during follow‐up should develop a comprehensive understanding of what it means to cope with a changed and challenging body. J. Surg. Oncol. 2016;113:229–234 . © 2015 The Authors. Journal of Surgical Oncology Published by Wiley Periodicals, Inc.